Kajian Teoritis Penentuan Tetapan Planck Menggunakan Model Elektrodinamika Maxwell - Zaada Faidullah, Ilmy; Sasongko, Dwi P.; Priyono, Priyono (BERKALA FISIKA, 2009)
Theory of Electromagnetism and Planck constant have important role in the development of light theory. Electromagnetism theory explains the velocity of light is constant and finite because light is phenomenon of propagation of Electromagnetism Wave. Distribution of Planck Radiation that introduces Planck constant also based on the theory of Electromagnetism, however, now light treated like as a particle. Planck constant not only radically changes concept of light but also has be main source of the birth of Modern Physics. An interesting thing to investigate connection between Maxwell equation that well known with concept of classically Physics and Planck constant, a constant that often used in Quantum Mechanics. Deriving Planck constant from Maxwell Equation can be done by understanding study of Radiation Quantization that based on the assumption. First, Electromagnetism wave is on the vacuum space so there is no charge and current. Second, Hamiltonian of Radiation stated by Hamiltonian of Harmonic Oscillation. Third, mass of Photon regarded does not affect Hamiltonian of Radiation because it is difficult to determine rest mass of Photon. Fourth, Dirac postulate used as non commutable multiplication rule of position and momentum coordinate. In this research has obtained an elaborate explanation deriving Planck constant from Maxwell equation that can be shorted as follow. From Maxwell equation will be derived Maxwell wave equation that consist of Vector Potential Fields. Its form similar with Harmonic Oscillation function so Hamiltonian Radiation can be stated as Hamiltonian of Harmonic Oscillation. By Using Dirac postulate, Oscillation Harmonics can be studied in Quantum Mechanic so will be obtainedÂ  Planck constant that contained on the Fourier Coefficient Operator. Â  Keywords : Maxwell Equation, Planck Constant, Fourier Coefficient Operator.